Penerapan Pendekatan Kontekstual dalam Pembelajaran Keterampilan Menulis Puisi pada Siswa Kelas X SMA PGRI 4 Kota Bogor - Sandi Budiana; Muhammad Nur Kamil (Triangulasi: Jurnal Pendidikan Kebahasaan, Kesastraan, Dan Pembelajaran, 2021)
This research aimed are to find out Contextual approach in Learning writing poetry and to find out the difficulties on  students of X grade SMA PGRI 4 Bogor in writing poetry. Experiment method is used in this research. Data collection are test, questionnaire and observation. Students of  X grade SMA PGRI 4 Bogor are population of this research. The sample of this research are experiment and controll class. Experiment treatment is X-2 grade IPA and Controll treatment is and  X-1 IPA 2 . To get the data is obtained through Cluster random sampling. The first hyphothesis is implementation of Contextual Teaching and Learning (CTL) which increases  writing poetry on students of X grade SMA PGRI 4 Bogor. It can proved based on the students’result of pretest and postest in experiment treatment is used Contextual Teaching and Learning (CTL) that is their improvement. Hyphotesis is students of  X  grade SMA PGRI 4 Bogor have barrier in writing poetry that is proved. Based on the result of students’ questionnare, they get barrier in writing poetry that is proved based on the 58,33% percentage, they difficult to choose words around 66,67%, then they difficult to choose vocabulary 66,67%, they use the proper and good words 66,67%, they conveys their feeling and idea to write poetry around 62,50%. Therefore, we concluded that Contextual Teaching and Learning (CTL) improves students to write poetry . Either they write poetry or  they get barrier to write poetry.